The Dynamics of Domestic Violence: Learning About the Match - Dan Anderberg; Noemi Mantovan; Robert M. Sauer (Institute of Labor Economics (IZA), 2021)
We present a dynamic lifecycle model of women's choices with respect to partnership status, labour supply and fertility when they cannot directly observe whether a given male partner is of a violent type or not. The model is estimated by the method of simulated moments using longitudinal data from the Avon Longitudinal Study of Parents and Children. The results indicate that uncertainty about a partner's abusive type creates incentives for women to delay fertility, reduce fertility overall, divorce more often and increase labour supply. We also study the impact of higher female wages, income support to single mothers, and subsidized childcare when the mother is working. While higher wages reduce women's overall exposure to abuse, both income support and subsidized childcare fail to do so because they encourage early fertility. Income support also leads to less accumulated labour market experience and hence higher abuse rates.
Keywords: J12; J13; 330; domestic violence; learning; fertility; ALSPAC